Fraction distribution of heavy metals and its relationship with iron in polluted farmland soils around distinct mining areas - Zhao, Wantong; Gu, Chunhao; Ying, Hong; Feng, Xionghan; Zhu, Mengqiang; Wang, Mingxia; Tan, Wenfeng; Wang, Xiaoming (Applied geochemistry, 2021)
Polluted farmland soils around mining areas are usually enriched in Fe (oxyhydr)oxides and various heavy metals (HMs), however, their interactions, essential to evaluate the mobility and availability of HMs, in such soils are poorly understood. In this study, HMs polluted farmland soils were collected from several typical mining areas distributed from the south to the center of China, with distinct soil physicochemical properties. We comparatively analyzed the chemical fractions of HMs and Fe in these soils and determined the association relationship between HMs and Fe fractions using chemical extraction and correlation analysis. Most soils contain multiple HMs like As, Cu, Pb, Zn, and Cd, with varying environmental risks across the regions. Excluding the residual fraction, Cu, Pb, and Cd mainly exist in the reducible fraction, while Zn predominately accumulates in the oxidizable fraction. The total Cu, Pb, and Zn exhibit positive correlations with their available contents (P < 0.01), suggesting that the availability of these HMs is predictable by their total contents. Additionally, the positive correlations among Pb, Zn and Cd indicate that these HMs are associated with each other. Arsenic in these soils is predominantly associated with various Fe fractions, while Cd shows a closer relationship with crystalline Fe oxides and probably locates in the mineral structure. Additionally, As and Cd exhibit significant positive correlations within various Fe oxides, suggesting a synergistic accumulation effect in these soils. These new insights into the fraction distribution of HMs and their association properties with Fe fractions are essential to ecological risk assessment and remediation of HMs in polluted farmland soils. [Display omitted] •Most studied soils contain multiple heavy metals pollutants with varying environmental risks at different regions.•Availability of Cu, Pb, and Zn is closely related to their total contents.•Pb, Zn, and Cd are associated with each other in mining soils.•Soil As is associated with various Fe oxides, while Cd shows a closer interaction with crystalline Fe oxides.•As and Cd exhibit a synergistic accumulation effect within various Fe oxides.